LITERATURE REVIEW ON THE ROLE OF TEACHERS IN INCREASING STUDENT LEARNING MOTIVATION IN SCHOOLS - Aulia Khairunisa; Ines Munajah; Agis Maulana; Selnistia Hidayani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
Education is a process that is carried out consciously and directed to improve the ability of students to become faithful, virtuous, intelligent, and skilled individuals. In the learning process, teachers have a very crucial role as facilitators, motivators, and supervisors in learning activities. One of the important elements that affect a student's learning success is the drive to learn. This study aims to analyze the contribution of teachers in increasing students' motivation to learn in schools through a review of the literature from a number of academic sources, including relevant national and international journals. This study uses a qualitative approach with a literature study method, where the researcher analyzes findings from previous research related to strategies, approaches, and elements that affect students' learning motivation. The results of the study indicate that the role of educators is crucial in fostering students' motivation to learn through the use of innovative teaching methods, good emotional approaches, giving appreciation and encouragement, and creating a comfortable and conducive learning atmosphere. Teachers not only act as material deliverers, but also as figures who can build good interpersonal relationships with students so as to foster confidence, responsibility, and motivation to continue learning. In addition, the role of teachers in providing positive feedback and guiding students to achieve learning goals greatly contributes to increasing their internal motivation. The results of this study conclude that teachers play an important role in creating meaningful learning experiences and encouraging students to achieve maximum achievements. This literature is expected to be a reference for educators and prospective teachers in understanding the significance of the role of teachers in encouraging student learning motivation and in designing creative learning strategies that focus on the needs of students